Dynamics of transition dipole moment orientation in representative fluorescent proteins - Khoroshyy, Petro; Martinez-Seara, Hector; Myšková, Jitka; Lazar, Josef (Physical chemistry chemical physics, 2023)
Molecules of fluorescent proteins (FPs) exhibit distinct optical directionality. This optical directionality is characterized by transition dipole moments (TDMs), and their orientation with respect to the molecular structures. Although our recent observations of FP crystals allowed us to determine the mean TDM directions with respect to the framework of representative FP molecules, the dynamics of TDM orientations within FP molecules remain to be ascertained. Here we describe the results of our investigations of the dynamics of TDM directions in the fluorescent proteins eGFP, mTurquoise2 and mCherry, through time-resolved fluorescence polarization measurements and microsecond time scale all-atom molecular dynamics (MD) simulations. The investigated FPs exhibit initial fluorescence anisotropies (r0) consistent with significant differences in the orientation of the excitation and emission TDMs. However, based on MD data, we largely attribute this observation to rapid (sub-nanosecond) fluorophore motions within the FP molecular framework. Our results allow improved determinations of orientational distributions of FP molecules by polarization microscopy, as well as more accurate interpretations of fluorescence resonance energy transfer (FRET) observations.
Keywords: Luminescent Proteins; Fluorescence Resonance Energy Transfer; Molecular Structure; Molecular Dynamics Simulation; molekulární struktura; Fluorescent Dyes; simulace molekulární dynamiky; luminescentní proteiny; rezonanční přenos fluorescenční energie; fluorescenční barviva